Evaluation of five Legionella urinary antigen detection kits including new Ribotest Legionella for simultaneous detection of ribosomal protein L7/L12. Issue 10 (October 2021) - Nakamura, Akihiro; Fukuda, Saori; Kusuki, Mari; Watari, Hideo; Shimura, Satoshi; Kimura, Keigo; Nishi, Isao; Komatsu, Masaru; ,
Abstract: Urinary antigen tests are a widely used rapid diagnostic method for Legionella pneumonia. However, conventional urinary antigen tests are unable to detect anything other than Legionella pneumophila serogroup 1. The Ribotest Legionella (Ribotest) can detect all serogroups by using antibodies recognizing L. pneumophila ribosomal protein L7/L12 in addition to the conventional L. pneumophila serogroup 1 lipopolysaccharide. The aim of this study was to evaluate the performance of Ribotest against conventional urinary antigen tests, including the detection of Legionellaceae other than L. pneumophila . We investigated the detection sensitivity of various kits using in-vitro culture-soluble antigen extracts of ATCC strains and 22 clinical isolates collected from multiple medical facilities in the Kinki region of Japan. For L. pneumophila serogroup 1, four kits, including Ribotest, had a detection sensitivity of 10 5  CFU/mL, with only Check Legionella having a sensitivity of 10 6  CFU/mL. L. pneumophila non-serogroup 1 and Legionellaceae of other species were undetectable by the four conventional kits, whereas Ribotest could detect them with a sensitivity of 10 5 –10 8  CFU/mL. The Ribotest was also able to detect other species such as Legionella hackeliae, Legionella feeleii, Legionella anisa, Fluoribacter bozemanae, and Fluoribacter dumoffii, but the detection sensitivity of L. hackeliae and L. feeleii was 10 8  CFU/mL, which was much lower than that of the other strains. The Ribotest has high potential to be applied as a rapid diagnostic method for pneumonia caused by other species of Legionella and Fluoribacter .